(untitled) (TEST Ticontre. Theory Text Translation, 2020)
The essay is related to Poetiche Perio-diche Sincroniche. The Italian poetry magazines of the 70s-90s, University of Trento, Department of Humanities (16-17 May 2019) and its focus is “Tam Tam”: a bizarre review directed and animated by Adriano Spatola, Giulia Niccolai and by other protagonists of the dynamic poetic scene of the late nineteenth century published on a quarterly basis from 1972 to 1989 with significant interruptions due both to the underground root of the magazine and to the self-financing policy that characterized the review, as for internal tensions among the editorial board. The article is divided into two parts: the first part delimits the historical-cultural context in which “Tam Tam” was born, it defines the prominent profiles in the editorial staff; it therefore provides a chronology and a physical description of the magazine (its formats and graphic peculiarities). The second part analyzes the contents of “Tam Tam”, particularly the complementarity of arts, intermedia and the visual poetry that informed the spatolian utopia of the “total poetry”. The essay moves from the historical, social and cultural landscape in which “Tam Tam” took shape, to the poetics of the magazine through the object-book, a vivid reflection of the poetic lines strongly supported by the “poetry workers” collected around the maison poétique of Bazzano. The information and documentation treated in the essay are linked by the work done by the author in his ongoing collaboration with C.I.R.C.E initiative, Department of Letters | University of Trento.